2021
DOI: 10.1002/pssr.202100236
|View full text |Cite
|
Sign up to set email alerts
|

Status of Al2O3/TiO2‐Based Antireflection and Surface Passivation for Silicon Solar Cells

Abstract: Inhibiting charge recombination effectively by surface passivation is very important for high‐efficiency silicon solar cells. With the emergence of passivated emitter and rear cells (PERCs), which surpass conventional solar cells, the need for a novel passivation scheme is increasing. Passivation layer stacks using negatively charged Al2O3 have been applied successfully to realize high‐efficiency PERC solar cells. Herein, the developments of surface passivation by Al2O3/TiO2‐based layers are reviewed. The topi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…8). As it is reported in the literature that the Al2O3 thin film has good silicon passivating properties, it was decided to investigate its influence on the short-circuit current [17]. Deposition of a passivating thin film has a positive effect on the short-circuit current value.…”
Section: Resultsmentioning
confidence: 99%
“…8). As it is reported in the literature that the Al2O3 thin film has good silicon passivating properties, it was decided to investigate its influence on the short-circuit current [17]. Deposition of a passivating thin film has a positive effect on the short-circuit current value.…”
Section: Resultsmentioning
confidence: 99%
“…Despite these merits, only a few studies evaluated and discussed the properties of solution-processed TiO x . Some of these works focused on the optical and electrical properties of a crystalline thick TiO 2 (over 40 nm) layer, which is a well-suited material for antireflection coating (ARC) application as it has a large refractive index and band gap. ,, Benefiting from a 60 nm TiO x layer on an n-type silicon substrate, Sun et al reported a high i V oc and an effective lifetime of 695 mV and 1.11 ms, respectively . Nevertheless, such a thick layer cannot be employed in the CSC structures, where ideally an amorphous thin layer of TiO x is in demand.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it enables high shape preservation and large-area preparation of thin films. Therefore, ALD technology was used to prepare Al2O3 films extensively [8], especially the application in optical thin film coating [9], electronic devices [10], anticorrosion coating [11], passivation layer on the surface of solar cells [12], antibacterial nanocoating [13], and so on. The complex and variable crystal structure of Al2O3 is mainly due to its strong Al-O bond and atomic spatial ordering.…”
Section: Introductionmentioning
confidence: 99%